Impact of Workplace Environmental Factors on Employee Commitment: Evidence from North East Nigeria - Funminiyi, Adeoye K. (International Journal of Scientific Research and Management (IJSRM), 2018)
Recently, it has been observed that workplace environmental factors are essential predictors of employee commitment, for achieving organizational goals and objectives. This study assessed the impact of workplace environmental factors on employee commitment in North East of Nigeria. Adopting a survey design, the research made used of primary data, collected mainly through administering a set of questionnaire to 205 management staff, supervisors and non-management staff of the selected manufacturing firms from Adamawa, Bauchi and Gombe states respectively. The findings revealed that: there is significant positive relationship between feedback and employee efficiency; incentive positively affects employees’ commitment. The study concluded that effective performance feedback is critical to employees’ efficiency and organisational growth. Incentives as key factor also contribute immensely to employee commitment in workplace. The work recommended that organisations should incorporate feedback approach into it system. In addition management should be consistent in giving incentives to workers that desire it on merit ground.